Revitalizing Village Religious Study Groups Through a Monthly Khatmil Qur’an Program: A Participatory Community Service Model in Senduro Village - Lianka Putri; Ihya' Ulumuddin (Khidmatuna : Jurnal Pengabdian Masyarakat, 2026)
Village religious study groups represent a long-standing form of non-formal Islamic education in rural Muslim communities. However, in Senduro Village, Lumajang Regency, their educational and social functions have weakened because of declining attendance, repetitive program formats, and limited community involvement in program governance. This community service article examines the revitalization of village religious study groups through a monthly khatmil Qur’an program integrated with thematic religious lectures and participatory reflection. The program employed Participatory Action Research (PAR), involving religious leaders, study-group administrators, and community members in problem identification, collaborative planning, implementation, reflection, and evaluation. Data were collected through participatory observation, informal interviews, documentation, and pre-test and post-test assessments covering three dimensions: revitalization of religious study activities, community participation and religious awareness, and program sustainability. Descriptive analysis showed an increase in the average score from 59% before the program to 85% after implementation. Improvements were evident in the regularity and diversity of religious study activities, congregational attendance, discussion participation, understanding of religious values, and collective commitment to continuing the program independently. These findings indicate that monthly khatmil Qur’an can function not merely as a ritual practice but as a participatory learning mechanism that strengthens non-formal Islamic education, social cohesion, and sustainable community-based religious engagement in rural settings. The model offers a practical framework for community service programs seeking to revitalize local religious traditions through dialogic, contextual, and community-owned educational practices.